2012
DOI: 10.1111/j.1600-6143.2012.04232.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower Calcineurin Inhibitor Doses in Older Compared to Younger Kidney Transplant Recipients Yield Similar Troughs

Abstract: The number of older adults undergoing kidney transplantation has increased, yet little is known about calcineurin inhibitor (CNI) metabolism in this group. We studied CNI troughs and doses to determine if there were age related differences in metabolism and dose requirements. We studied 348 young (18–34 years), 1831 middle (35–64 years) and 374 older (65–84 years) adult kidney transplant recipients enrolled in a 7-center prospective study. Troughs were obtained from each patient 2x/week in weeks 1–8 and 2x/mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 34 publications
7
67
1
1
Order By: Relevance
“…Aged male C57BL/6 mice (18 months of age) treated with tacrolimus require only half the weight-adjusted dose to achieve trough levels found in young (2-3 months of age) murine skin recipients (46). These results are consistent with a prior prospective clinical study that found that recipients older than 65 years required half the body weight-adjusted dose to achieve therapeutic tacrolimus trough levels (92). CD4 + T cells isolated from the in aged mice (78).…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nsupporting
confidence: 81%
“…Aged male C57BL/6 mice (18 months of age) treated with tacrolimus require only half the weight-adjusted dose to achieve trough levels found in young (2-3 months of age) murine skin recipients (46). These results are consistent with a prior prospective clinical study that found that recipients older than 65 years required half the body weight-adjusted dose to achieve therapeutic tacrolimus trough levels (92). CD4 + T cells isolated from the in aged mice (78).…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nsupporting
confidence: 81%
“…Jacobson et al [65] also found a similar trend. Elder recipients had higher normalized cyclosporine pre-dose concentrations than middle aged or young adults, despite receiving median doses that were 100 mg/day lower, and recipient age had the largest effect on cyclosporine troughs [65]. These data suggest that in the elderly patient it might be better to reduce the starting dosage and aim at lower whole blood cyclosporine target concentrations.…”
Section: Cyclosporinesupporting
confidence: 56%
“…In addition, the effect of age within a given genotype was still substantial. In recipients with the CYP3A5 * 3/ * 3 genotype (CYP3A5 non-expressers), dose and weight normalized predose concentrations were 45% higher in the elder subjects compared to the younger adults; meanwhile, a similar increase in predose concentration with increasing age was also observed in individuals with the CYP3A5 * 1/ * 1 or * 1/ * 3 genotype (CYP3A5 expressers) [65]. These data suggest that the dose requirement of tacrolimus in elderly patients might be much less than the younger patients when aiming for the same target concentration range.…”
Section: Tacrolimusmentioning
confidence: 49%
See 2 more Smart Citations